Effect of indigenously developed nano-hydroxyapatite crystals from chicken egg shell on the surface hardness of bleached human enamel: An In Vitro study - Divya Kunam; Vidhya Sampath; Sujatha Manimaran; Mahalaxmi Sekar (Wolters Kluwer Medknow Publications, 2019)
Objective: The objective was to evaluate the effect of nano-hydroxyapatite (nHA) derived from chicken eggshell on bleached human enamel in comparison with commercial casein phophopeptide-amorphous calcium phosphate (CPP-ACP) paste using Vickers microhardness test. Materials and Methods: nHA powder was prepared from chicken eggshell using combustion method. nHA slurry was prepared by mixing 1.8 g of nHA powder with 0.3 ml of distilled water. Forty intact maxillary anterior teeth were collected and decoronated, and the crowns were embedded in acrylic mold with the labial enamel surfaces exposed. Baseline microhardness evaluation was done (T0). The specimens were randomly divided into the following four groups (n = 10) based on the surface treatment of enamel: Group 1: no bleaching treatment; Group 2: bleaching with 30% hydrogen peroxide (HP) solution; Group 3: bleaching followed by the application of CPP-ACP; and Group 4: bleaching followed by the application of nHA. The specimens were stored in artificial saliva at 37°C for 2 weeks, after which they were subjected to Vickers microhardness test (T14). One-way ANOVA and Tukey's post hoc multiple comparison tests were used for statistical analysis (P < 0.05). Results: Bleaching with HP significantly decreased the enamel microhardness. CPP-ACP and nHA derived from chicken eggshell increased the enamel microhardness significantly. There was no significant difference in microhardness values among the CPP-ACP and nHA groups. Conclusion: Nano-hydroxyapatite sourced from chicken eggshell was as effective as CPP-ACP in remineralizing and restoring the lost microhardness of bleached enamel.